Digital crowdsourcing: Unleashing its power in rheumatology - Krusche, Martin; Burmester, Gerd R.; Knitza, Johannes (Annals of the Rheumatic Diseases, 2020)
The COVID-19 pandemic forces the whole rheumatic and musculoskeletal diseases community to reassemble established treatment and research standards. Digital crowdsourcing is a key tool in this pandemic to create and distil desperately needed clinical evidence and exchange of knowledge for patients and physicians alike. This viewpoint explains the concept of digital crowdsourcing and discusses examples and opportunities in rheumatology. First experiences of digital crowdsourcing in rheumatology show transparent, accessible, accelerated research results empowering patients and rheumatologists.
CRIS-Team Scopus Importer:2020-09-11
Keywords: health services research; outcome and process assessment; health care; outcome assessment; health care; quality indicators; health care